Synthesis and anti-inflammatory and analgesic activities of 2,4-di-n-butyl-3,5-diarylimino-1,2,4-thiadiazolidines - Pandeya S.N.; Naik P.R.; Singh S.; Singh P.N. (My University, 2025)
Ten 1,2,4-thiadiazolidines were synthesized and screened for their anti-inflammatory and analgesic activities. Butyl isothiocyanate was used as a starting material. Several compounds showed significant anti-inflammatory and analgesic activities. The unsubstituted and o-methyl, p-acetoxy and o-chloro substituted compounds were found to be more potent anti-inflammatory and analgesic agents than the other compounds. © 1991 The Pharmaceutical Society of Korea.